Effects of Cardiopulmonary Rehabilitation in a Patient with Rheumatoid Arthritis and Post Pulmonary Tuberculosis Co-infection and COVID-19: A case study (Research, Society and Development, 2021)
Objective: To report the effects of a rehabilitation protocol in a patient with rheumatoid arthritis and post-coinfection of pulmonary tuberculosis and COVID-19. Materials and methods: Descriptive exploratory case study, conducted in the state of Pará, in the city of Belém. Data collection was carried out by the researchers using evaluation and evolution forms used by the physiotherapist during treatment and for analysis were exams such as computed tomography, radiography, spirometry and hemograms, performed through medical consultations, are used. Peripheral manual muscle strength, Maximum Inspiratory Pressure (PImax.) and Maximum Expiratory Pressure (PEmax.), functional capacity, lung capacity, quality of life and functionality, respectively, were evaluated using the Medical Research Council (MRC) scale, manovacuometry, spirometry , 6-minute walk test (6MWT), generic quality of life questionnaire EQ-5D (5-dimensional EuroQol) and Functional Independence Measure (FIM) ladder, collected at two different times, at the beginning of rehabilitation and at the end of the treatment. Results: The cardiopulmonary rehabilitation protocol improved MIP. at 157.1% and the PEmax. In 5.55%, functional capacity in 77.7% and quality of life in 30% compared to the values ​​initially presented. Conclusion: Cardiopulmonary rehabilitation showed a positive impact on improving the global function of the respiratory and cardiac systems of patients with rheumatoid arthritis and post-coinfection of pulmonary tuberculosis and COVID-19, through a rehabilitation protocol.